2022
DOI: 10.1007/s12144-021-02412-0
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of personal and ecological assets: Adolescents’ motivation and engagement in self-driven learning

Abstract: While opportunities for adolescents to drive their own learning are increasing, differences in motivations for and engagement in these opportunities are rarely investigated. The current study employed a sample of adolescents ( N = 580, M age = 16.53) enrolled in GripTape , a 10-week self-driven learning program in which youth pursue topics of their choosing. Cluster analysis classified adolescents based on their personal (e.g., r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
4
0
4
Order By: Relevance
“…Many studies have reported that LM significantly impacts SE (Black & Deci, 2000;Fredricks et al, 2017;Wang & Eccles, 2013). Also, some researchers have found a mediating role of LM between PAS and SE (Benita et al, 2021;Yoo, 2015;Zhu & Burrow, 2022). Thus, the current study suggests that college students might have higher learning motivation when they perceive more teacher autonomy support, which would increase their engagement.…”
Section: Introductionmentioning
confidence: 52%
“…Many studies have reported that LM significantly impacts SE (Black & Deci, 2000;Fredricks et al, 2017;Wang & Eccles, 2013). Also, some researchers have found a mediating role of LM between PAS and SE (Benita et al, 2021;Yoo, 2015;Zhu & Burrow, 2022). Thus, the current study suggests that college students might have higher learning motivation when they perceive more teacher autonomy support, which would increase their engagement.…”
Section: Introductionmentioning
confidence: 52%
“…As Zhu and Burrow (2022) found, personal traits had a significant impact on young learners’ motivation. A relevant question posed here is how demographics influence teenagers’ learning motivation.…”
Section: Introductionmentioning
confidence: 93%
“…Często osiągnięcie wytyczonego celu łączy się z jakąś nagrodą lub wiąże z chęcią uniknięcia kary. W literaturze przedmiotu odnotowujemy liczne próby wytłumaczenia osobistych i społecznych uwarunkowań motywacji, różni autorzy akcentują jej wielorakie aspekty (Gollwitzer 2020;Hansell 1989;Zhu, Burrow 2023). Główne pytanie niniejszych rozważań dotyczy związku pomiędzy aktywnością młodzieży a psychologicznymi i pedagogicznymi aspektami motywacji, rozumianej jako istotna siła inicjująca i podtrzymująca podjęte działania.…”
Section: IIunclassified